Organizational stressors associated with job stress and burnout in correctional officers: a systematic review - Finney Caitlin; Stergiopoulos Erene; Hensel Jennifer; Bonato Sarah; Dewa Carolyn S (BMC, 2013)
Abstract Background In adult correctional facilities, correctional officers (COs) are responsible for the safety and security of the facility in addition to aiding in offender rehabilitation and preventing recidivism. COs experience higher rates of job stress and burnout that stem from organizational stressors, leading to negative outcomes for not only the CO but the organization as well. Effective interventions could aim at targeting organizational stressors in order to reduce these negative outcomes as well as COs' job stress and burnout. This paper fills a gap in the organizational stress literature among COs by systematically reviewing the relationship between organizational stressors and CO stress and burnout in adult correctional facilities. In doing so, the present review identifies areas that organizational interventions can target in order to reduce CO job stress and burnout. Methods A systematic search of the literature was conducted using Medline, PsycINFO, Criminal Justice Abstracts, and Sociological Abstracts. All retrieved articles were independently screened based on criteria developed a priori. All included articles underwent quality assessment. Organizational stressors were categorized according to Cooper and Marshall's (1976) model of job stress. Results The systematic review yielded 8 studies that met all inclusion and quality assessment criteria. The five categories of organizational stressors among correctional officers are: stressors intrinsic to the job, role in the organization, rewards at work, supervisory relationships at work and the organizational structure and climate. The organizational structure and climate was demonstrated to have the most consistent relationship with CO job stress and burnout. Conclusions The results of this review indicate that the organizational structure and climate of correctional institutions has the most consistent relationship with COs' job stress and burnout. Limitations of the studies reviewed include the cross-sectional design and the use of varying measures for organizational stressors. The results of this review indicate that interventions should aim to improve the organizational structure and climate of the correctional facility by improving communication between management and COs.